Zenith oasis / Noor Aina Farisha Ibrahim ... [et al.] - Ibrahim, Noor Aina Farisha; Mohamed, Abdul Hamid; Saidi, Dianna Nur A’ain; Muhammad, Afzanizam (2024)
In the realm of outdoor furniture design, fusion timber represents a pivotal convergence of aesthetic innovation and sustainability. This abstract investigates the transformative potential of fusion timber in redefining outdoor furniture as both visually captivating and environmentally responsible. Through an analysis of design processes, material sourcing, and manufacturing techniques, this study elucidates how fusion timber integrates seamlessly into the creation of outdoor furniture that transcends mere functionality to embody principles of ecological stewardship. By examining industry trends and consumer preferences, this abstract emphasizes the growing importance of fusion timber as a catalyst for sustainable design practices in the outdoor furniture sector. Through its unique blend of natural beauty and environmental consciousness, fusion timber emerges as a cornerstone in reshaping the landscape of outdoor furniture, offering a compelling synthesis of form, function, and sustainability. This abstract thus highlights the pivotal role of fusion timber in advancing the dialogue on responsible design and underscores its potential to revolutionize the way we perceive and interact with outdoor spaces.